2018
DOI: 10.3390/nu10091305
|View full text |Cite
|
Sign up to set email alerts
|

Bergamot Polyphenol Fraction Exerts Effects on Bone Biology by Activating ERK 1/2 and Wnt/β-Catenin Pathway and Regulating Bone Biomarkers in Bone Cell Cultures

Abstract: Epidemiological studies show that fruit consumption may modulate bone mineral density. However, data regarding the effect of the Citrus bergamia Risso (Bergamot orange), a citrus fruit containing a high concentration of flavonoids, on bone health are still lacking. In this study, we investigated the effects of Bergamot polyphenols on the Wnt/β-catenin pathway in two distinct bone cell types (Saos-2 and MG63). Findings showed that exposure to 0.01 and 0.1 mg/mL doses upregulate β-catenin expression (p = 0.001),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Furthermore, when miR-27b-3p was overexpressed, the expression of CTNNB1 decreased, which confirmed our previous hypothesis. In agreement with these findings, the relationship between CTNNB1 and endometriosis has been reported in several studies [ 29 , 30 , 31 , 32 ], which is related to the Wnt and the ERK1/2 pathways [ 33 , 34 ]. To the best of our knowledge, CTNNB1 [ 11 ] plays an important role in the adhesion, invasion, and metastasis of endometrial tissues via the Wnt/β-catenin signaling pathway and could even improve the border of extraovarian endometriosis lesions [ 35 ].…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, when miR-27b-3p was overexpressed, the expression of CTNNB1 decreased, which confirmed our previous hypothesis. In agreement with these findings, the relationship between CTNNB1 and endometriosis has been reported in several studies [ 29 , 30 , 31 , 32 ], which is related to the Wnt and the ERK1/2 pathways [ 33 , 34 ]. To the best of our knowledge, CTNNB1 [ 11 ] plays an important role in the adhesion, invasion, and metastasis of endometrial tissues via the Wnt/β-catenin signaling pathway and could even improve the border of extraovarian endometriosis lesions [ 35 ].…”
Section: Discussionsupporting
confidence: 81%
“…BPF also reduces RANKL expression, suggesting that it may inhibit osteoclastogenesis. Further studies are necessary to validate this study [35].…”
Section: Further Beneficial Impacts Of the Bergamot-derived Polypheno...mentioning
confidence: 79%
“…Neutralization of the bone-specific WNT inhibitor is currently being evaluated as a promising anabolic therapy for patients with osteoporosis [34]. A study by Pujia et al (2018) examined the effects of bergamot polyphenols in bone cell models and showed that RUNX2, β-catenin, ERK 1/2, and intracellular COL1A proteins are up-regulated by exposure to increasing doses of BPF. In addition, the expression of RANKL, which is a known stimulus for increased osteoclast activity, is reduced in these cells, suggesting that BPF decreases RANKL and may play a potential role in bone resorption.…”
Section: Further Beneficial Impacts Of the Bergamot-derived Polypheno...mentioning
confidence: 99%
“…To date, the protective effects of the main polyphenols contained in high concentration in bergamot are well-known. In particular, important beneficial effects on the nervous system [ 41 , 42 , 43 ], the mineralization of bones [ 44 ], the regulation of keratinocytes [ 45 ], the regulation of the metabolism [ 46 , 47 ], against adipose-tissue inflammation [ 48 ] and during myocardial regeneration [ 49 ] were reported. These protective effects of bergamot have been found in many of its formulations: extract (BE), juice (BJ), essential oil (BEO), and polyphenolic fraction (BPF).…”
Section: Introductionmentioning
confidence: 99%